Formulation of Novel Microbial Consortia for Rapid Composting of Biodegradable Municipal Solid Waste: An Approach in the Circular Economy: 10.32526/ennrj/22/20230270 - Wijerathna, P. A. K. C.; Udayagee, K. P. P.; Idroos, F. S.; Manage, Pathmalal M. (Environment and Natural Resources Journal, 2024)
Urbanization and rapid industrialization have led to the escalation of municipal solid waste generation and accumulation. Composting is widely recognized as a sustainable solution for solid waste management. However, its long-term investment is considered a disadvantage. The present research study discusses the rapid biotransformation of solid waste into valorized compost. Bacteria were isolated from soil, solid waste, and leachate samples from open dump sites. From the 18 different bacterial consortia created using potential isolates, the five most promising consortia were selected based on concurrent different enzyme production. These selected consortia were incorporated into typical compost bins with Municipal Solid Waste (MSW). Daily monitoring of enzymatic activity, pH, conductivity, bulk density, moisture, and temperature, along with other composting parameters, was conducted. The study’s results demonstrated that consortium No. 5, comprising Bacillus haynesii, Bacillus amyloliquefaciens, and Bacillus safensis, exhibited significant (p<0.05) enzyme activity of cellulase, amylase, lipase and proteinase enzymes during composting compared to the control and other treatment setups. Consortium No. 5 also facilitated rapid and successful composting, as evidenced by significant alterations of composting parameters by exhibiting a shorter average composting time, reducing it from 110±10 days to 20±3 days, showcasing the potential applicability of formulated bacterial consortium as a sustainable and greener approach to the global solid waste problem. The novelty of this study lies in the isolation of local bacterial strains from open dump sites soil, MSW, and MSW leachate samples, which were then utilized in the composting organic fraction of MSW, enhancing the potential for effective waste management.